2019
DOI: 10.1016/j.tranon.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-34b/c rs4938723 and TP53 Arg72Pro Polymorphisms with Neuroblastoma Susceptibility: Evidence from Seven Centers

Abstract: Neuroblastoma is a pediatric malignancy arising from the developing peripheral nervous system. p53 and downstream effector miR-34b/c have critical tumor suppressing functions. TP53 Arg72Pro (rs1042522 C > G) and miR-34b/c rs4938723 (T > C) polymorphisms have been known to modify cancer susceptibility. This study was performed to validate the association of these two polymorphisms and neuroblastoma risk with 819 cases and 1780 controls. Odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…To our knowledge, the association between miR34b/c and Wilms tumor susceptibility has not been investigated. miR34b/c has been shown to be intimately connected to the development and prognosis of a variety of tumors, including gastric cancer, bladder cancer, pancreatic cancer, ovarian cancer, prostate cancer, hepatocellular carcinoma, neuroblastoma and many others [31][32][33][34][35]. In our previous study, we found that miR34b/c rs4938723 T>C polymorphism has a protective effect on neuroblastoma [36].…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, the association between miR34b/c and Wilms tumor susceptibility has not been investigated. miR34b/c has been shown to be intimately connected to the development and prognosis of a variety of tumors, including gastric cancer, bladder cancer, pancreatic cancer, ovarian cancer, prostate cancer, hepatocellular carcinoma, neuroblastoma and many others [31][32][33][34][35]. In our previous study, we found that miR34b/c rs4938723 T>C polymorphism has a protective effect on neuroblastoma [36].…”
Section: Discussionmentioning
confidence: 90%
“…In several existing studies, variations in TP53 have been significantly associated with susceptibility to various pediatric tumors. Of which, TP53 Pro/Pro genotype was associated with increased susceptibility to acute lymphoblastic leukemia in Caucasian children [ 48 ], TP53 rs1042522 CG/GG genotype had a significantly increased risk of Wilms tumor in children under 18 months of age [ 49 ], and TP53 rs1042522 CG/GG genotype was associated with reduced susceptibility to neuroblastoma [ 50 ]. Meanwhile, mutations in TP53 affect tumor treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 44 This polymorphism was subsequently found to be associated with the risk of developing neuroblastoma and Wilms’ tumor but not hepatoblastoma among Chinese children. 19 , 21 , 34 However, there remains a lack of valuable evidence depicting the association between the polymorphism and the integrated risk of pediatric malignant abdominal solid tumors. To the best of our knowledge, only one study has investigated this particular association by genotyping 101 pediatric solid tumors samples and 202 controls; Borbora et al identified an SNP pair composing of TP53 rs1042522 and p21 cip1 rs1059234 that had a significant impact on the risk of developing pediatric solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 16 This gene encodes a 393 amino-acid–long protein that is critical for regulating the cell cycle and executing tumor suppressing functions by orchestrating of the transcriptional activation of tumor-associated genes involved in apoptosis, maintenance of genetic stability, and angiogenesis. 17 - 19 Alterations in this gene have been extensively studied in a variety of human malignancies, including pediatric malignant solid tumors. 20 The fact that the Single Nucleotide Polymorphism Database hosts information regarding >1000 TP53 single nucleotide polymorphisms (SNPs) supports the highly polymorphic nature of this gene.…”
Section: Introductionmentioning
confidence: 99%